An Assessment of Nutritional Deficiency Symptoms in the Tea Plant (Camellia sinensis L.) Through Field Survey - Kanij Fatema Tuz Zohora; Apu Biswas (Turkish Journal of Agriculture: Food Science and Technology)
The most important factor in both plant development and productivity, which mostly depends on nutrient availability in the soil and environment, is the constituents of soil nutrients. Soil is always losing its nutrients by leaching, surface runoff as well as through harvesting and cultural operations like: pruning. For maintaining the balance of agricultural ecosystem fertilizer application is necessary to improve soil condition and gain better yield. In case of tea industry for maintaining better and uniform production applying fertilizer is a widespread management technique in worldwide. Tea requires a lot of macro and micronutrients for growth because it cannot be grown without the usage of fertilizer and other nutrient supplies. The purpose of this field survey was to ascertain the nutritional condition of tea leaves as well as the signs of nutrient deficiencies in tea plants. In this study, deficiency symptoms of the essential nutrients were found out at different tea estates of Moulvibazar and Sylhet districts as well as photographs were taken. Photographs of the nutrient deficient tea plants were correlated with the established symptoms. The range of total nitrogen, phosphorus, potassium, calcium, magnesium and zinc content in the collected tea leaf samples were 2.95- 5.18%, 0.28- 0.49%, 0.56-1.88%, 0.12-0.49%, 0.07-0.08% and 0.002- 0.004%, respectively.